CONCEPTUAL MODELLING AND ORGANIZATION OF SECURITY MECHANISMS IN DISTRIBUTED SYSTEMS - T. Galibus; V. Krasnoproshin (Informatika)
We analyze the existing DS from the point of security and construct a two-level hierarchy of models. Such approach allows us to separate the abstraction (architecture) level and the concrete (component) level of ISS. The core set of methods, i. e. authentication and key exchange protocols, corresponds to the abstraction level and is defined as security infrastructure (SI). The final security parameters optimization and additional mechanisms such as authorization, routing and data auditing of the protection mechanisms are configured on the component level of the DS. In addition, we outline the systematic step-by-step ISS configuration method.